Asian Nursing Research Maret 2014 - Redaksi (Elsevier, 2014)
- Predictors for Successful Smoking Cessation in Korean Adults - Health Behaviors and Risk Factors Associated with Chronic Kidney Disease in Korean Patients with Diabetes: The Fourth Korean National Health and Nutritional Examination Survey - Problems of Clinical Nurse Performance Appraisal System: A Qualitative Study - ...